Holding the Line: Maintaining Indigenous Sovereignty and Authority in International Research Collaborations - Hetaraka, Maia; Meiklejohn-Whiu, Selena; Webber, Melinda; Jesson, Rebecca (Taylor and Francis Group, 2026)
This article calls to attention the possibilities and problematics of upholding Indigenous ethics and approaches in cross-cultural international research collaborations. We describe the opportunities and challenges that present themselves and elaborate on four lessons learned during a recent education project, including (1) how the authority and mana of Indigenous stakeholders can be maintained, (2) how to ensure Indigenous concepts and worldviews are honoured, (3) how to decolonize western academic expectations about open data-sharing, and (4) how and why Indigenous rituals of encounter must be established to ensure cultural safety. Using Moana Jackson’s (2016) ten Māori research ethics, this paper identifies and examines what needs to be upheld, interrogated and refused when working in cross-cultural international research collaborations. We conclude with recommendations for collaborators, including the importance of embedding regular opportunities for collective reflexivity, as a means of rebalancing or refusing the uneven power relations that affect genuine partnership.
Keywords: 1303 Specialist Studies in Education; 1608 Sociology; Education; 3902 Education policy, sociology and philosophy; 3903 Education systems; 3904 Specialist studies in education; Indigenous ethics; cross-cultural research collaboration; worldviews; decolonization; Māori